Kajian peraturan daerah Kabupaten Pangandaran nomor 14 tahun 2015 tentang penyelenggaraan kepariwisataan di Kabupaten Pangandaran terhadap pembentukan kompepar - Susilo Budi Winarno; Endang Widayati; Erna Wigati; Kaswan Hermawan (STIE Pariwisata API Yogyakarta, 2023)
Pangandaran is one of the regencies with the greatest potential in the tourism sector, where the tourism sector is the leading sector that generates the largest regional income for the Pangandaran Regency. Regional tourism potential that is used as a tourist object and attraction can be in the form of natural conditions, flora, fauna, regional culture of Pangandaran Regency and national culture both in the form of ideas, social life or in the form of the work of the people in Pangandaran Regency. To achieve this, the role of the community in tourism development in Pangandaran Regency through Kompempar must accommodate the aspirations of all tourist destination objects in Pangandaran Regency. This is in accordance Pangandaran Regency Regional Regulation Number 14 of 2015 concerning the Implementation of Tourism in Pangandaran Regency.